SALES DATA PROCESSING IN BOOK STORES MAHASURI USING MICROSOFT VISUAL BASIC 6.0 - Maryani Maryani; Yuce Yuliani, SKom, MM Yuce Yuliani, SKom, MM (Jurnal Sistem Informasi, 2002)
At the present time the technology has advanced with his street had taken the time tomake everything easy to grow and all can be done quickly and precisely. Moreover,with an additional tool in the form of a computer to make all that had been long donemore quickly and conveniently. Computer tools can we find anywhere, either inoffices or in shops. Like shopping in the sales transactions are still conducted bymanual count manualisasi with tools made ineffective because it can inhibit the salestransaction at the time. For example in mahasuri bookstore sales are in the system andmaking monthly reports manulisasi done, so the data required to support operationalprocesses often experience delays and will be a lot of mistakes,It needs to be made a database on the system sales of books and making its report andit need a program to run the database. So that all can be controlled either in systemsales as well as the preparation of reports for each month.